Optimisation of Oxygen Treatment Parameters for Eucalyptus tereticornis Kraft Pulps - Bhandari, K. S.; Bhatnagar, Anju (Indian Forester, 2001)
Eucalyptus tereticornis was subjected to kraft pulping using 12, 14, 16, 18% active alkali at 25% sulphidity level. It yielded 44.70, 49.70, 46.40 and 46.00% screened pulps, corresponding to kappa number 56.34, 44.91, 32.69 and 26.46, respectively. The pulps corresponding to kappa number 44.91 and 26.46 were evaluated for strength properties and subjected to oxygen treatment at 6,8,10 kg/cm2 oxygen pressure and 90, 100, 110 and 120°C temperature for 60 minutes. 0.00, 1.25,2.50,3.75 and 5.00% alkali was charged during oxygen treatment, in each case. Pulp yield, kappa number and brightness of pulps were determined, in each case and results were analysed. It was observed that at 3.75% and 2.50% alkali charge for pulp corresponding to kappa number 44.91 and 26.46, respectively, the kappa numbers were decreased to 21.32 and 13.05 at 8 kg/cm2 oxygen pressure and 60 minutes reaction time. Thus considered to be sufficient to achieve about 50% (about 50% drop in kappa numbers) delignification. Further, the pulps produced at different temperature, 90, 100, 110 and 120°C under optimise conditions of oxygen pressure and alkali charge were evaluated for strength properties. On the basis of the data obtained, 100°C oxygen treatment temperature was found to be optimum. Results are discussed in this paper.